Impact of Digital Marketing Strategies, Brand Image, and Influencers on Netflix Purchase Decisions - Hidayat, Rizky; Ambarwati, Rita (LPPM Universitas Trunojoyo Madura, 2024)
The research was conducted to analyze the influence of digital marketing strategies, brand image, and influencers on purchasing decisions for Netflix products. The study was analyzed using the questionnaire spread method to find out the significant outcomes of Netflix usage decisions as well as the impact of brand image and digital marketing on the social community. The results of this study showed that each variable has a strong influence on Netflix usage decisions. This can be seen from the results of acquisition and data processes that show significant value, starting with digital marketing that is well branded by the influencer so that Netflix users get information digitally easily